Time lagged investigation of entrepreneurship school innovation climate and students motivational outcomes: Moderating role of students’ attitude toward technology - Yuan, Xuemei; Kaewsaeng-on, Rudsada; Jin, Shuai; Anuar, Marhana Mohamed; Shaikh, Junaid M.; Mehmood, Saqib (Frontiers in Psychology, 2022)
Based on the reinforcement theory of motivation, the purpose of this research was to measure the effect of school innovation climate on students' motivational outcomes, including behavioral engagement, academic self-efficacy, interest, and utility value. Furthermore, the conditional influence of students’ attitude towards technology on the link between school innovation climate and students' motivating outcomes has been investigated and reported. Data were gathered from the 305 entrepreneurship program students of five different universities located in China. In the SamrtPLS 3.3.3 program, the analysis was carried out using SEM. Results revealed that the school innovation climate has a favorable impact on improving the motivating outcomes of students. Additionally, results also provided support for moderation hypotheses that "students' attitude towards technology" moderated the relationship between "school innovation climate" and academic self-efficacy. On the contrary, “students' attitudes about technology”, did not appear to be a significant moderator in terms of enhancing the influence of the "school innovation atmosphere" on the students' behavioral engagement, interest, and utility value. This study provides key policy and theoretical implications as well as future research avenues for entrepreneurial school managers and education scholars.